Newly qualified doctors' perceptions of informal learning from nurses: implications for interprofessional education and practice. Issue 5 (9th May 2013) - Burford, Bryan; Morrow, Gill; Morrison, Jill; Baldauf, Beate; Spencer, John; Johnson, Neil; Rothwell, Charlotte; Peile, Ed; Davies, Carol; Allen, Maggie; Illing, Jan
Abstract: Newly qualified doctors spend much of their time with nurses, but little research has considered informal learning during that formative contact. This article reports findings from a multiple case study that explored what newly qualified doctors felt they learned from nurses in the workplace. Analysis of interviews conducted with UK doctors in their first year of practice identified four overarching themes: attitudes towards working with nurses, learning about roles, professional hierarchies and learning skills. Informal learning was found to contribute to the newly qualified doctors' knowledge of their own and others' roles. A dynamic hierarchy was identified: one in which a "pragmatic hierarchy" recognising nurses' expertise was superseded by a "normative structural hierarchy" that reinforced the notion of medical dominance. Alongside the implicit learning of roles, nurses contributed to the explicit learning of skills and captured doctors' errors, with implications for patient safety. The findings are discussed in relation to professional socialisation. Issues of power between the professions are also considered. It is concluded that increasing both medical and nursing professions' awareness of informal workplace learning may improve the efficiency of education in restricted working hours. A culture in which informal learning is embedded may also have benefits for patient safety.